Thinking about starting a franchise business? Think again - Carmen Cotei; Joseph Farhat (The Journal of Entrepreneurial Finance (JEF), 2024)
This study aims to explain the survival and exit outcome of franchise startups compared to other types of startups. Small business owners choosing to become franchisees have high expectations about business survival since "franchise is a proven business model that carries less risk." Using the Kauffman Firm Survey, we examine the survival patterns and M&A exit outcomes of a large sample of U.S. independent and franchise businesses started in 2004 and tracked over time for eight years. Our study provides unique results on the likelihood of survival and M&A exit of franchises relative to other startups. Although franchise businesses start larger, are very well-capitalized, and are led by highly educated owners, we find no significant difference in the survival rate between franchises and independent businesses. However, our results show a significant difference between the survival rate of franchises and those businesses started by purchasing "existing" firms. When the outcome is an M&A exit, the results show that franchises are 2.77 times more likely to exit via M&A than independent businesses, whereas "existing" businesses are 1.81 times more likely to exit via M&A than independent businesses. Overall, this study sheds more light on the controversial evidence on the survival and exit prospects of a large cohort of U.S. franchises, independent new businesses, and "existing" businesses.
Keywords: C41; C83; M13; 650; survival; M&A exit; franchise; startups; survey